Local Wisdom-Based Tourism Zoning in Yaro Wora Village, East Nusa Tenggara - Hannif Andy Al Anshori; An Nuur Khairune Nisa; Dina Oktavia; Reiza Dienaputra; Bambang Hermanto; Heru Nurasa; Awaludin Nugraha; Kasno Pamungkas (Badan Riset dan Inovasi Nasional (BRIN), 2026)
Yaro Wora traditional village, located in West Sumba Regency, East Nusa Tenggara Province, is a unique cultural landscape rich in indigenous wisdom, but it lacks a solid scientific basis for spatial planning and tourism zoning. The absence of empirical studies on customary-based tourism zoning has hindered the creation of an integrative model linking cultural preservation with tourism development. This study aims to formulate a cultural protection strategy for Yaro Wora by developing a tourism zoning framework rooted in local values, indigenous knowledge, and traditional Sumbanese spatial organization. Using a qualitative participatory approach, the research combines Participatory Rural Appraisal (PRA) and Focus Group Discussions (FGDs) to understand community perceptions of sacred, communal, and public spaces. Data were gathered through observation, interviews, and documentation, and then analyzed thematically through spatial ethnography and participatory planning principles. Findings show that implementing Community Use Zones (CUZs), including core multifunctional areas, critical linkage areas, and service connectivity areas, creates a spatial management system that harmonizes ecological, cultural, and spiritual dimensions. This zoning model functions as both a cultural heritage protection tool and a governance framework supporting ecological sustainability and community empowerment. The study strengthens conceptual and empirical foundations for adaptive, inclusive, and equitable tourism zoning policies rooted in local wisdom within Sumba’s indigenous communities.